Use of mobile apps for periodic knowledge tests and qualification assessment of slingers - Egelskaya, E. V.; Kalanchukova, V. A. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2022)
Introduction. The article is devoted to the issues of improving the processes of periodic knowledge testing and assessing the qualifications of slingers to improve the level of professional skills, readiness to use appropriate devices, equipment and personal protective equipment.Problem Statement. In view of the often formal organization of regular (periodic) knowledge checks of slingers, which potentially leads to accidents at work, there is a need to apply new forms of organization and conduct of these activities.Theoretical Part. Periodic knowledge testing involves an oral examination in the commissions of the organizations that operate cranes. As an alternative to regular knowledge checks, the independent qualification assessment at Qualification Assessment Centers is of particular importance. Taking into account the widespread digitalization of production and the widespread use of IT technologies, it is proposed to develop and apply mobile applications for periodic knowledge checks of slingers, allowing them to visualize and choose the right solutions for performing labor functions.Conclusions. The high level of professional training of the slinger is an important component in the issue of increasing the level of safety in the operation of lifting structures, so special attention must be paid to the training of qualified personnel.